2016
DOI: 10.1098/rspb.2016.0553
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic species diversity reveals biogeographic support for the ‘mountain passes are higher in the tropics’ hypothesis

Abstract: The 'mountain passes are higher in the tropics' (MPHT) hypothesis posits that reduced climate variability at low latitudes should select for narrower thermal tolerances, lower dispersal and smaller elevational ranges compared with higher latitudes. These latitudinal differences could increase species richness at low latitudes, but that increase may be largely cryptic, because physiological and dispersal traits isolating populations might not correspond to morphological differences. Yet previous tests of the MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 82 publications
3
80
1
2
Order By: Relevance
“…Further, our findings of a monotonic decrease in the thermal optima and lower minima of species and communities located at higher elevations, partially confirms our second hypothesis (Figures b and b). Yet, we found no relationship between species niche breadths and elevation nor with community breadth score and elevation, as opposed to Janzen's hypothesis (Janzen, ) and the results recently reported for cryptic aquatic insects (Gill et al, ). This suggests that the seasonality gradient is more strongly associated with species and community thermal niche breadth than summit elevation in tropical alpine systems.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Further, our findings of a monotonic decrease in the thermal optima and lower minima of species and communities located at higher elevations, partially confirms our second hypothesis (Figures b and b). Yet, we found no relationship between species niche breadths and elevation nor with community breadth score and elevation, as opposed to Janzen's hypothesis (Janzen, ) and the results recently reported for cryptic aquatic insects (Gill et al, ). This suggests that the seasonality gradient is more strongly associated with species and community thermal niche breadth than summit elevation in tropical alpine systems.…”
Section: Discussioncontrasting
confidence: 99%
“…We suspect the lack of annual thermal seasonality in equatorial mountain summits creates more constant conditions throughout the year, which could allow the presence of a more diverse array of biogeographical species groups including Tropical montane, Tropical Andean alpine and Páramo endemic species (Figure c). Complementary, the results of Gill et al () that shows the effect of the CVH along the elevation gradients became evident when only the cryptic species were considered in the analyses. Thus, a similar pattern could arise in our dataset if we only look at narrow‐range species restricted to alpine habitats across the Andes.…”
Section: Discussionmentioning
confidence: 62%
“…The authors found that cryptic species were homogeneously distributed among taxa and regions and concluded “that cryptic metazoan diversity can be treated as random error in biodiversity assessments.” Their meta‐analysis was later criticized for several methodological problems (Trontelj & Fišer, ), and additional analyses almost a decade later suggested that cryptic species actually may be heterogeneously distributed across animal phyla (Pérez‐Ponce de León & Poulin, ). The evidence for homogenous distribution of cryptic species across geographic regions is conflicting (Eme et al., ; Gill et al., ; Voda, Dapporto, Dinca, & Vila, ); perhaps an heterogeneous distribution can be detected only at global geographic scales.…”
Section: Cryptic Diversity In Biodiversity Researchmentioning
confidence: 99%
“…As a consequence, we can predict that physiological barriers to dispersal will be stronger for thermally specialized forest species, and as a corollary, forest species will have narrower elevational ranges than open‐habitat species (Ghalambor et al., ; Sheldon et al., ). Janzen's hypothesis pertains latitudinal comparisons between mountains (Gill et al., ; Polato et al., ). Our hypothesis is derived from the same underlying physiological principle; species are adapted to temperatures normally encountered in their temporal and geographical habitat or microhabitat (Janzen, ).…”
Section: Introductionmentioning
confidence: 99%